Development of Learning Media Using the Articulate Storyline Application in Integrated Thematic Learning - Aulia Alfirzan; Yalvema Miaz; Risda Amini; Hadiyanto (Jurnal Penelitian Pendidikan IPA, 2024)
This research is motivated by the conventional nature of learning that takes place in the classroom, that is, it is still teacher-centered, not student-centered. This research aims to produce learning media using the Articulate Storyline application in integrated thematic learning that is valid, practical and effective to improve student learning outcomes in class III elementary schools. This research uses research and development (R&D) methods with the ADDIE development model which has five stages, namely Analysis, Design, Development, Implementation, Evaluation. At the analysis stage, observations and interviews were carried out with teachers and students in elementary schools, at the design stage a learning media was designed according to the data and facts obtained. At the development stage of the learning media that has been designed, validation is carried out to find out whether the product is valid for application. Validation is carried out in three stages: first, validation by five validators who are experts in their respective fields with an overall average result of 88 with a very valid category. The results obtained after evaluating the practicality test of the teacher response questionnaire obtained an average score of 91 in the very practical category, and the student response questionnaire obtained an average score of 90 which was in the very practical category. In the effectiveness test, the learning results obtained an average value of 89 in the effective category and for the N-Gain Score an average value of 0.74 was obtained with a percentage of 74, including the effective category. Based on the results of validity, practicality and effectiveness tests, it can be concluded that the learning media using the Articulate Storyline Application in thematic learning is a valid, practical and effective learning media.